2021
DOI: 10.1111/cogs.13011
|View full text |Cite
|
Sign up to set email alerts
|

Model‐Based Wisdom of the Crowd for Sequential Decision‐Making Tasks

Abstract: We study the wisdom of the crowd in three sequential decision-making tasks: the Balloon Analogue Risk Task (BART), optimal stopping problems, and bandit problems. We consider a behavior-based approach, using majority decisions to determine crowd behavior and show that this approach performs poorly in the BART and bandit tasks. The key problem is that the crowd becomes progressively more extreme as the decision sequence progresses, because the diversity of opinion that underlies the wisdom of the crowd is lost.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…In the present study, we were primarily interested in how individuals correct beliefs and behavioral intentions after receiving feedback about their own risk misestimation, as opposed to population-wide risk estimation biases. Our findings align with prior studies on the “wisdom of the crowd,” which have shown that averaging variable and inaccurate estimates from many individuals can produce remarkably accurate estimates [ 40 – 42 ].…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, we were primarily interested in how individuals correct beliefs and behavioral intentions after receiving feedback about their own risk misestimation, as opposed to population-wide risk estimation biases. Our findings align with prior studies on the “wisdom of the crowd,” which have shown that averaging variable and inaccurate estimates from many individuals can produce remarkably accurate estimates [ 40 – 42 ].…”
Section: Discussionsupporting
confidence: 90%
“…Also, (Derakhshan Beigy, 2019) suggested that sentiment analysis of the English dataset is more effective and efficient than the Persian dataset for predicting the stock market. The most straightforward approach to merging individual conduct is for the multitude to imitate most individuals in every attempt (Thomas et al, 2021). It is imperative to acknowledge that while the foundation of investor conduct is logical reasoning, they, for diverse reasons, cannot assimilate all the information available in the stock market (Noroozi et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas there is ample evidence for the validity of wisdom of crowds in general (Davis-Stober et al, 2014;Larrick & Soll, 2006;Surowiecki, 2004), this assumption may be inadequate under certain conditions. For instance, judgment processes can lead to non-normal distributions (Hueffer et al, 2013;Lorenz et al, 2011;Lorenz, 2021) or extreme judgments (Thomas et al, 2021) in which the mean of the judgments does not longer reflect the correct answer. However, for the present purpose of comparing the accuracy of independent and dependent judgments, this is not a critical assumption given that it is made both for wisdom of crowds and for sequential collaboration (skewed distributions are considered in the empirical study below).…”
Section: Modeling Independent Judgmentsmentioning
confidence: 99%